Juan Rulfo, o no hay salvación ni en la vida ni en la muerte - Lyon, Thomas C. (Revista Chilena de Literatura, 2016)
A pesar de la secularización del siglo XX, Juan Rulfo aprovecha una rica tradición religiosa en todo lo que escribe. En el discurso religioso se destaca un fondo de culpabilidad, de deseo de confesar y recibir perdón, y de imposibilidad de cualquiera clase de salvación. Sin entender este fondo religioso el estudio de la obra de Rulfo queda incompleto. Despide the secularization of the 20th century, Juan Rulfo makes use of a rich religious tradition in all his writings. A background of guilt, of the desire to confess and to be pardoned, and of the impossibility of any kind of salvation is emphasized in the religious discourse. If this religious background is not understood, any study of Rulfo's work is incomplete.